2019
DOI: 10.17582/journal.jahp/2019/7.2.70.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera (Moringa) Supplementation via Urea Molasses Multi-nutrient Moringa Block (UM3B) on Nutrient Intake and Utilization in Bali Cattle

Abstract: The objective of the study was to determine the effect of Moringa oleifera supplementation via Urea Molasses Multi-nutrient moringa Block (UM3B) on consumption and digestibility of dry matter and organic matter in the Bali cattle. A total of 16 Bali cattle aged 2-4 years, of same sex ratio, body weight around 200-250kg was used in this study. The cows were allotted to four equal groups that were placed in individual cages rendered to the distribution of treatment groups. The feed was given in the form of field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The second group was control, consisted of 5 cows that were not given UM3B. The composition/formulation and nutritional content of UM3B were adopted from [3]. The basic feed given to all livestock was in the form of forage feed from field grass and elephant grass feed of about 10% of body weight, additional feed in the form of bran 1 kg/head/day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second group was control, consisted of 5 cows that were not given UM3B. The composition/formulation and nutritional content of UM3B were adopted from [3]. The basic feed given to all livestock was in the form of forage feed from field grass and elephant grass feed of about 10% of body weight, additional feed in the form of bran 1 kg/head/day.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of Moringa in UMMB becomes Urea Molasses Multi-nutrient Moringa Block (UM3B). Furthermore, [3] reported that the addition of UM3B supplement had an effect on the consumption and digestibility of Balinese cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Complete replacement of Berseem hay in the ration of lactating cows with 20% M. oleifera stems showed the best feed conversion and nutrient digestibility, leading to superior milk yield and composition (El-Esawy et al, 2018). Malik et al (2019) concluded that the consumption and digestibility of dry matter and organic matter were improved by supplementation with M. oleifera in Bali cows. Shankhpal et al (2019) found a similar tendency, and stated that cows fed 15 kg Moringa green fodder had higher milk yields, significantly more milk fat, lactose, and b-Carotene, but reduced cholesterol content compared to the control group (Figure 1).…”
Section: Use In Cattle Feedingmentioning
confidence: 97%